Dogs' Demographic Characteristics Associated with Relationship Differences Perceived by the Guardian - Videla, Marcos Díaz; Olarte, María Alejandra (European Scientific Journal, ESJ, 2017)
Dogs are the most popular animal species in our culture, probably because of their higher tendency to establish emotional and affective roles with humans. Even though the identification of factors that influence in the human-animal relationship may contribute to improve the human and animal wellbeing, few studies have investigated which dogs’ characteristics influence in the quality of this relationship. A descriptive study was carried out by means of surveys aiming to describe the demographic characteristics of companion dogs that are associated with the perception of the relation quality by their guardians. An incidental sample of 425 dogs’ guardians was taken in the city of Buenos Aires, who filled out a questionnaire with six relational intensity measures: Dog-Owner Interaction, Perceived Emotional Closeness, Perceived Costs, Anthropomorphism, Willingness to Adapt, Perceived Benefits. Dogs’ age was associated with lower scores in interaction and perceived benefits and costs. Dogs’ size was associated with higher benefits and will to adaptation by guardians, without association with costs perception. Dogs of specific breeds differentiated from those of mixed breeds only in terms of a higher interaction behavior linked to the incorporation of the animal in social activities. No differences were observed related to the dog’s breed nor its reproductive status. The associations identification carried out may direct the selection of a dog for adoption, as well as help the development and upkeep of successful human-dog relationship. Potential applied implications are delineated. Human-dog relationship develops mainly at an emotional level, with little involvement of cognitive and social components that increase the complexity of relationships among humans.